Electronic Portfolio Assessment Instruments in Improving Students' Creative Thinking Skills - Rahmawati, T.; Mulyaningsih, T.; Nahadi, N.; Suhanda, H.; Lee, W. K.; Aziz, H. A.; Anwar, S. (Jurnal Pendidikan IPA Indonesia, 2023)
The objective of the study is to determine the stage of the process of developing electronic portfolio assessment instruments and obtain a valid and reliable electronic portfolio assessment instrument that can be used as an alternative effective assessment in improving students’ creative thinking on redox reaction materials. The research method employed was Research and Development (RD) with a 4-D development model: define, design, develop, and disseminate. The data sources for this study were obtained from chemistry education lecturers, chemistry teachers, and eleventh-grade students in one of the high schools in Bandung. The instruments used in this study were interview guidelines, instrument content validation sheet, task assessment observation sheet, creative thinking skills assessment task and rubric, portfolio assessment rubric, pre-test and post-test questions and rubrics on chemical reaction equations that have tested for validity. The developed electronic portfolio assessment instrument was realized in a task and assessment rubric based on 21st-century creative thinking indicators. The results reveal that the developed electronic portfolio assessment instrument has good quality because it fulfils the valid requirements with a CVR value of 1.00 and fulfils the reliable requirements with a Cronbach Alpha value of 0.702-0.982. Electronic portfolios can be used as one of the assessment tools for science learning. The developed electronic portfolio assessment instrument may promote students’ creative thinking on redox reaction material based on the N-Gain 0.72 with the high category and has good effectiveness based on the N-Gain 0.61 with the medium category. Based on the category of mastery learning, the effectiveness is 9.66%.